(untitled) (Indian Journal of Child Health, 2022)
Objectives: To determine whether or not, all breastfed newborns should get preventive iron (up to age of 6 months). It will determine the disease burden and clinicopathological profile of anemia in infants up to 6 months and its correlation with maternal Hb levels. Materials and Methods: A 4-month hospital-based cross-sectional study was conducted in all infants under the age of 6 months and their mothers admitted to the pediatric ward of a tertiary health care center in the Sub-Himalayan region. Results: About 42% of infants (up to 6 months of age) and 64% of mothers were found to be anemic. It was found that mothers of 74% of total anemic infants were also anemic. Furthermore, in 79% cases mothers with good ferritin stores (?12 ng/ml) also have infants with good ferritin levels (?10 ng/ml). It was found that mothers who have not consumed adequate amount of iron in their pregnancy, 44% of them have anemic infants. Despite the fact that the association between newborn and maternal characteristics is not statistically significant, the results are noteworthy, indicating the need for a more comprehensive investigation to determine the relationship. Conclusion: High rates of anemia in early life point to the need of multicentric as well as population-based study so that we can collect evidence to start iron prophylaxis in this highly vulnerable developing age group of 0–6 months. Further higher rates of anemia in mothers warrant the strengthening in the implementation plan of iron and folic acid supplementation to all females of reproductive age group.